Durable Ru Nanocrystal with HfO2 Modification for Acidic Overall Water Splitting - Kong, Xiangkai; Xu, Jie; Ju, Zhicheng; Chen, Changle (Nano-Micro Letters, 2024)
Durable and efficient bi-functional catalyst, that is capable of both oxygen evolution reaction and hydrogen evolution reaction under acidic condition, are highly desired for the commercialization of proton exchange membrane water electrolysis. Herein, we report a robust L-Ru/HfO2 heterostructure constructed via confining crystalline Ru nanodomains by HfO2 matrix. When assembled with a proton exchange membrane, the bi-functional L-Ru/HfO2 catalyst-based electrolyzer presents a voltage of 1.57 and 1.67 V to reach 100 and 300 mA cm-2 current density, prevailing most of previously reported Ru-based materials as well as commercial Pt/C||RuO2 electrolyzer. It is revealed that the synergistic effect of HfO2 modification and small crystalline domain formation significantly alleviates the over-oxidation of Ru. More importantly, this synergistic effect facilitates a dual-site oxide path during the oxygen evolution procedure via optimization of the binding configurations of oxygenated adsorbates. As a result, the Ru active sites maintain the metallic state along with reduced energy barrier for the rate-determining step (*O→*OOH). Both of water adsorption and dissociation (Volmer step) are strengthened, while a moderate hydrogen binding is achieved to accelerate the hydrogen desorption procedure (Tafel step). Consequently, the activity and stability of acidic overall water splitting are simultaneously enhanced. Highlights: 1 Heterostructure constructed via confining crystalline ruthenium nanodomains by hafnium dioxide matrix was fabricated through a two-step annealing method for overall water splitting. 2 The synergistic effect of hafnium dioxide modification and small crystalline domain formation significantly alleviates the over-oxidation of ruthenium.